Draft Five Year Plan - Orissa 1978-83 Vol. I - Planning Commission (Planning Commission, 1978)
The estimates of National and State Income data suffer from many inadequacies, yet they are important indices of measurement of economic growth. The State income at constant prices is a measure of the net domestic product in real terms. The following table would show the growth of State income and per capita income in Orissa over the last decade and a half, at 1960-61 prices and at current prices. Growth rate—During the last fifteen years (1961—75) the State Income of Orissa increased at the annual rate of 3-8 per cent (Compound) whereas the per capita income increased at the rate of 1'5 per cent (compound) annually. The rate of growth of the State Income of Orissa has been 4'6 per cent in the Third Plan, 5'3 per cent during the three Annual plans, 2'6 per cent in the Fourth Plan and 2'5 per cent in the Fifth Plan. Compared to earlier plans, the growth-rate during the Fourth and Fifth Plans was very low, partly due to the low levels of investments and partly due to the severe inflation prevailing all over the country, which might have brought down the real value of investments much lower.
Draft Five Year Plan 1978-83 Vol. I
Government of Orissa